An Empirical Analysis of the Determinants of Child Poverty in European Countries - Nazmiye Tekdemir; Hakki Hakan Yilmaz (Transylvanian Review of Administrative Sciences, 2024)
The main objective of the study is to analyze the significance of the determinants of child poverty before and after social transfers and to assess how child poverty differs from adult poverty. In the empirical part of the study, the panel data analysis method is used for a total of 12 years and 31 European countries between 2006-2017. The main findings of the study show that GINI coefficient, per capita income, female employment, household size and property status of the dwelling are significant determinants of child poverty. The empirical finding reveals that in the selected countries, the impact of social transfers in reducing child poverty is more limited than the impact of social transfers in reducing adult poverty and that social protection programs should be designed and implemented more intensively to reduce child poverty. The study suggests that to combat child poverty in EU countries, it is necessary to review social programs that focus on child inequality programs in a multi-sectoral framework with a view to designing more effective public policies.